Recovery of Valuable Metals from Fly Ash via Hydrometallurgy Method for Li-ion Battery Anode Material - Cornelius Satria Yudha; Enni Apriliyani; Tika Paramitha; Windhu Griyasti Suci; Himmah Sekar Eka Ayu Gustiana (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Coal-derived fly ash, or CFA, is a harmful waste for humans. CFA waste handling by its processing and utilization has become the most promising approach, which not only decreases the waste's hazard level but also improves its economic potential. This research aims to recover metals from CFA and utilize them as anode material for Li-ion batteries. Iron, magnesium, aluminum, and calcium are retrieved from the CFA via a two-step hydrometallurgical method, i.e., acid leaching followed by alkaline precipitation. The leaching process utilizes various acids, such as acetic acid (CH3COOH), hydrochloric acid (HCl) and sulfuric acid (H2SO4). Metal precipitation is carried out using sodium hydroxide solution (NaOH). Morphological and quantitative metal composition analysis are investigated using a scanning electron microscope and energy dispersive spectroscopy (SEM-EDX). The physical and chemical properties of the as-prepared samples are characterized using Fourier-transformed Infra-red spectroscopy (FTIR) and Thermal Gravimetry-Differential Thermal Analysis (TG/DTA). Based on the analysis, iron, magnesium and calcium are successfully recovered in a mixed hydroxide precipitate. The type of acid affects the final morphology and composition of the product. Therefore, our approach can be considered effective in CFA waste processing and producing high-quality product.